Penyuluhan Rumah Sehat Dalam Rangka Meningkatkan Kualitas Hunian Di Desa Lembah Sari Kecamatan Batu Layar Kabupaten Lombok Barat - Pujiastuti, Heni; Fitrayuda, Adryan; Efendy, Anwar; Hidayati, Nurul; Hamdani, Hafiz; Fariyadin, Adiman; Pascanawati, Maya Saridewi; Isfanari, Isfanari; Partono, Agus; Irawan, Feri; Haryadi, Febrian Ekasapta; Amaelisa, Viara (Pendidikan Matematika, FKIP Universitas Mataram, 2023)
Sidemen Lauq Hamlet is one of the hamlets in Lembah Sari Village, Batu Layar District, West Lombok Regency. The houses of the residents of this hamlet do not yet reflect healthy homes; the houses are close together, seem damp, there is not enough sunlight, the animal cages are close to the residents' houses, daily living needs use Sidemen River water, defecation in the river, and throwing rubbish in the drainage channel. The aim of this outreach activity is to provide residents with an understanding of the importance of healthy homes and a healthy environment. The method used in this counseling is a presentation using PowerPoint slides and interactive discussions. The implementation of community service was carried out for one day on August 28, 2023. Residents were enthusiastic about attending counseling. This is because the male residents are farmers and planters who are still resting after returning from work, while the female residents are housewives. The implementation of the counseling went well and smoothly. The outreach activities increase the knowledge of the residents of Sidemen Lauq Hamlet regarding healthy homes and make the residents of Sidemen Lauq Hamlet aware of the importance of healthy homes. With this outreach, it can become a medium for health promotion, which is expected to have a positive impact on increasing knowledge among the community, especially about healthy homes.